2007
DOI: 10.1016/j.cub.2007.03.069
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Gene Phylogenies Support the Monophyly of Cryptomonad and Haptophyte Host Lineages

Abstract: Cryptomonad algae acquired their plastids by the secondary endosymbiotic uptake of a eukaryotic red alga. Several other algal lineages acquired plastids through such an event [1], but cryptomonads are distinguished by the retention of a relic red algal nucleus, the nucleomorph [2]. The nucleomorph (and its absence in other lineages) can reveal a great deal about the process and history of endosymbiosis, but only if we know the relationship between cryptomonads and other algae, and this has been controversial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 42 publications
7
100
1
Order By: Relevance
“…Our analyses failed to support the monophyly of Archaeplastida and Chromalveolata because one putative chromalveolate group, the haptophytes, robustly branches within the Archaeplastida, as a sister to either the green plants or the rhodophytes. A similar position was recovered in other recent phylogenomic analyses (21,23). Our data filtering experiments intended to minimize LBA showed that this artifact is unlikely to be responsible for this positioning of haptophytes.…”
Section: Internal Excavata Relationships-the Jakobids Include Andalucsupporting
confidence: 54%
See 1 more Smart Citation
“…Our analyses failed to support the monophyly of Archaeplastida and Chromalveolata because one putative chromalveolate group, the haptophytes, robustly branches within the Archaeplastida, as a sister to either the green plants or the rhodophytes. A similar position was recovered in other recent phylogenomic analyses (21,23). Our data filtering experiments intended to minimize LBA showed that this artifact is unlikely to be responsible for this positioning of haptophytes.…”
Section: Internal Excavata Relationships-the Jakobids Include Andalucsupporting
confidence: 54%
“…Worse, in some cases single genes had been transferred laterally between the lineages under examination (12). More recently, the availability of vast quantities of data from genome-sequencing and expressed sequence tag (EST) projects over a wide range of eukaryotes has allowed phylogenetic estimation from ''supermatrices'' of moderate (13)(14)(15) to large (16)(17)(18)(19)(20)(21)(22)(23) numbers of genes. Although such phylogenomic approaches are less sensitive to stochastic error, they can, when the phylogenetic model is misspecified, reinforce systematic errors such as LBA, yielding apparently strong support for an incorrect phylogeny (16,19,24).…”
mentioning
confidence: 99%
“…5 and Figs. S7A and S8) and is consistent with the horizontal replacement of rpl36 in their plastid genomes (28) and analyses of nuclear genes (29,30). Many analyses recovered a monophyletic lineage including all red algal derived plastids (the chromalveolates), but this is not as strongly supported as the alveolate/ heterokont or hacrobian groupings.…”
Section: Plastid Phylogeny Supports a Common Origin Of Alveolate Andmentioning
confidence: 66%
“…Second, the addition of katablepharids to a phylogenomic dataset and its strong grouping with cryptophytes created the opportunity to test the position of the KC group by alternatively removing one of its members, which is of interest since cryptophytes branched with haptophytes in previous analyses of smaller datasets without katablepharids [22,24]. The removal of R. truncata led to no topological change, suggesting that the polyphyly of hacrobians was not simply due to adding katablepharid data (electronic supplementary material, figure S3).…”
Section: (C) How Robust Is This New Topology?mentioning
confidence: 99%
“…Nuclear-based phylogenomics have consistently shown that stramenopiles and alveolates are closely related, and that they form a strongly supported group with Rhizaria, altogether making the so-called SAR group [20,21]. At the same time, haptophytes and cryptophytes generally appeared together, albeit with less support and only when relatively large alignments are used [21][22][23][24]. Based on congruent plastid and nuclear data, these were proposed to be a second chromalveolate lineage, Hacrobia [25].…”
Section: Introductionmentioning
confidence: 99%